Using stated preferences data to analyze preferences for full and partial retirement - Arthur van Soest; Arie Kapteyn; Julie M. Zissimopoulos (Institute for the Study of Labor (IZA), 2007)
Structural models explaining retirement decisions of individuals or households in an intertemporal setting are typically hard to estimate using data on actual retirement decisions, since choice sets are for a large part unobserved by the researcher. This paper describes an experiment in which both perceived retirement opportunities and preferences for retirement are measured. For the latter, respondents evaluate how attractive they find a number of hypothetical, simplified, retirement trajectories involving early retirement, late retirement, and gradual retirement, each with its own corresponding income path. The questions were fielded in the Dutch CentERpanel. The answers are used to estimate a stylized structural life-cycle model of retirement preferences. The results suggest that, for example, many respondents could be convinced to work part-time after age 65 before retiring completely at age 70 for a reasonable financial compensation. Simulations combining the information on perceived opportunities with estimated preferences illustrate the importance of employer imposed restrictions on retirement and the scope for increasing labor force participation of the elderly by creating opportunities for gradual retirement.
urn:nbn:de:101:1-20080401452
Keywords: 330; Flexible Altersgrenze; Altersgrenze; Offenbarte Präferenzen; Niederlande